2011
DOI: 10.2165/11538980-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole as Adjunctive Therapy for Patients with Major Depressive Disorder

Abstract: Aripiprazole was initially approved to treat schizophrenia and later approved for bipolar mania, as a monotherapy and an adjunctive therapy (manic or mixed episodes), and for irritability associated with autism. Aripiprazole is a partial agonist at dopamine D(2) and D(3) and serotonin 5-HT(1A) receptors, and is an antagonist at 5-HT(2A) receptors. This profile, and convincing preliminary data from small-scale studies, provided the rationale for the large-scale exploration of aripiprazole for unipolar depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 99 publications
2
81
1
Order By: Relevance
“…Based on placebo controlled clinical trials, aripiprazole has clearly shown efficacy as an augmentation therapy [13]. However, it is also associated with more adverse events (AEs) than antidepressant monotherapy in patients with MDD [13].…”
Section: Currently Available Atypical Antipsychotics For Major Depresmentioning
confidence: 99%
“…Based on placebo controlled clinical trials, aripiprazole has clearly shown efficacy as an augmentation therapy [13]. However, it is also associated with more adverse events (AEs) than antidepressant monotherapy in patients with MDD [13].…”
Section: Currently Available Atypical Antipsychotics For Major Depresmentioning
confidence: 99%
“…It is also known that dopamine activity in the frontal cortical area is impaired in depression 8 . Preclinic data supports that aripiprazole may be effective in depression treatment through partial dopamine agonism and 5-HT antagonism [40][41][42][43] . In studies with animal depression models, depression was shown to be related to dopaminergic deficiency and this condition may be reversed by dopamine agonists 8 .…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the use of anticholinergic agents for MDD patients is recommended to be short term with early discontinuation, particularly for Asians with their greater vulnerability to anticholinergic AEs. In fact, the most common interventions associated with EPS resolution were dose reduction of aripiprazole (51 %) and no intervention (36 %), in registration clinical trials of aripiprazole for MDD [7].…”
Section: Clinical Points For the Use Of Atypical Antipsychotics For Mmentioning
confidence: 99%
“…Consideration of different pharmacodynamic profiles, including affinity on various neurotransmitters and monoamine receptors among each atypical antipsychotic (AA), should also be beneficial for controlling such florid symptoms of MDD when current antidepressants are not adequately effective, especially concerning patient clinical status [7]. According to a recent pooled analysis, quetiapine significantly reduced the symptoms of generalized anxiety disorder, with improvements beginning from week 1; quetiapine also has a favourable profile on sleep disturbance for MDD patients [8].…”
mentioning
confidence: 99%